Association Between Body Mass Index, Abdominal Obesity and Menopause-Related Symptoms in Postmenopausal Women - Brianna A Rice; Patricia Heavey (SURE Journal: (Science Undergraduate Research Experience Journal))
Abstract: Existing research demonstrates a lack of data on the relationship between body mass index (BMI) and menopause-related symptoms in postmenopausal women, particularly in Ireland. This study aimed to determine whether there is an association between BMI, general abdominal obesity and menopause-related symptoms in postmenopausal women. This should help bridge the data gap regarding postmenopausal women living in Ireland and their symptoms. Introduction: Menopause is defined as the permanent cessation of a woman's menstrual cycle. This is caused by a reduction of the secretion of oestrogen and progesterone, leading to reduced ovarian function. These changes have been attributed to many psychological, vasomotor and urogenital symptoms such as hot flushes, sleep problems, vaginal dryness, anxiety and exhaustion. Weight gain and body shape changes also occur at this stage of life, although it has not always been directly linked to the menopause. A woman is considered postmenopausal once she has not experienced a period in 12 months. Evidence suggests that there is a potential association between body weight, general abdominal obesity and menopause-related symptoms in postmenopausal women. Methods: This was a cross-sectional study that recruited postmenopausal women. The participants were assessed using validated questionnaires on lifestyle habits and menopausal symptoms using the Menopausal Rating Scale. Participants height, weight and waist circumference were also measured in the health sciences lab on the TUS campus. Results: Of the 26 postmenopausal women, 26.92% (n=7) had a healthy BMI, 38.46% (n=10) were overweight and 34.62% (n=9) were obese. Waist circumference measurements showed that 11.54% (n=3) had a low risk of obesity-related conditions, 7.69% (n=2) were at risk and 80.77% (n=21) were at significant risk. It was found that participants who were obese (10.67±3.80) had significantly higher psychological MRS scores compared to participants who had a healthy BMI (6.57±0.90) (p=0.02). Those women who were meeting the physical activity guidelines were also more likely to report a lower MRS and somatic symptom score (pConclusions: The findings from this study are exploratory but suggest there may be a potential relationship between BMI and psychological menopausal symptoms. Further research in this area using a larger sample size is warranted.